A new method for assessing the contribution of Primary Biological Atmospheric Particles to the mass concentration of the atmospheric aerosol. (February 2016) - Perrino, Cinzia; Marcovecchio, Francesca
Abstract: Primary Biologic Atmospheric Particles (PBAPs) constitute an interesting and poorly investigated component of the atmospheric aerosol. We have developed and validated a method for evaluating the contribution of overall PBAPs to the mass concentration of atmospheric particulate matter (PM). The method is based on PM sampling on polycarbonate filters, staining of the collected particles with propidium iodide, observation at epifluorescence microscope and calculation of the bioaerosol mass using a digital image analysis software. The method has been also adapted to the observation and quantification of size-segregated aerosol samples collected by multi-stage impactors. Each step of the procedure has been individually validated. The relative repeatability of the method, calculated on 10 pairs of atmospheric PM samples collected side-by-side, was 16%. The method has been applied to real atmospheric samples collected in the vicinity of Rome, Italy. Size distribution measurements revealed that PBAPs was mainly in the coarse fraction of PM, with maxima in the range 5.6–10 μm. 24-h samples collected during different period of the year have shown that the concentration of bioaerosol was in the range 0.18–5.3 μg m − 3 (N = 20), with a contribution to the organic matter in PM10 in the range 0.5–31% and to the total mass concentration of PM10 in the range 0.3–18%. The possibility to determine the concentration of total PBAPs in PM opens up interesting perspectives in terms of studying the health effects of these components and of increasing our knowledge about the composition of the organic fraction of the atmospheric aerosol. Graphical abstract: Highlights: We propose a method to quantify bioaerosol content in atmospheric particulate matter. The method is based on DNA/RNA staining and observation at epifluorescence microscopy. Bioparticle recognition and sizing are performed by an image analysis software. We found that bioaerosol mass contributes 0.3–18% of the mass concentration of PM. Most bioaerosol particles are found in the coarse fraction of the atmospheric aerosol.